Morphological variability in selected heterocystous cyanobacterial strains as a response to varied temperature, light intensity and medium composition - Zapomelová, E; Hrouzek, P; Reháková, K; Sabacká, M; Stibal, M; Caisová, L; Komárková, J; Lukesová, A (Folia microbiologica, 2008)
The effect of temperature, light and nutrient composition on morphological traits was determined in seven nostocacean cyanobacteria (Anabaena planctonica, A. sphaerica var. conoidea, A. spiroides, Aphanizomenon gracile, Nostoc sp., Scytonema sp., and Tolypothrix sp.). Their morphological variability was high but only some of the features showed changes reflecting varied growth conditions. The frequency of heterocyst occurrence decreased with increasing nitrogen concentration. Within the range studied, the effect of temperature on heterocyst frequency of Tolypothrix sp. and planktonic Anabaena strains could be fitted by a normal curve with a clear optimum while linear correlation was found in Aphanizomenon gracile. T-and S-type branching was observed in both Scytonema sp. and Tolypothrix sp. strains. T-type branching was found to be markedly dependent on nitrogen concentration. The abundance of necridic cells of Tolypothrix sp. increased linearly with temperature and light intensity. Regularity of trichome coiling of A. spiroides depended on culture medium, suggesting that nutrient composition may be the main controlling factor. In contrast, the effect of the experimental conditions on the dimensions of vegetative cells and heterocysts was weak. Their variability was markedly higher within each experimental treatment than between treatments.
Keywords: dusík; světlo; Temperature; půdní mikrobiologie; Culture Media; teplota; Light; Soil Microbiology; Cyanobacteria; kultivační média; sinice; Nitrogen